Assessment of the innovative quality of agomelatine through the Innovation Assessment Algorithm - Civalleri, Liliana; Licata, Sabrina (Farmeconomia. Health economics and therapeutic pathways, 2012)
Aim: the aim of this study was to assess the innovative quality of a medicine based on agomelatine, authorized by the European Commission through a centralized procedure on 19th February 2009 and distributed in Italy under the brands Valdoxan® and Thymanax®. Methodology: the degree of innovation of agomelatine was determined through the Innovation Assessment Algorithm (IAA), which considers the innovative quality of a medicine as a combination of multiple properties. The algorithm may be represented as a decision tree, with each branch corresponding to a property connected with innovation and having a fixed numerical value. The sum of these values establishes the degree of innovation of the medicine. The IAA is articulated in two phases: the first assesses the efficacy of the drug based on the clinical trials presented in support of the registration application (IAA-efficacy); the second reconsiders the degree of innovation on the basis of the efficacy and safety data resulting from clinical practice once the drug has been placed on the market (IAA-effectiveness). Results and conclusions: the score obtained for agomelatine was 592.73 in the efficacy phase and 291.3 in the effectiveness phase. The total score for the two phases was 884, which is equivalent to a good degree of innovation for the molecule